Quality of working length radiographs taken and used by dental students during endodontic treatment. Issue 1 (2013) - Jayasinghe, R. D.; Weerakoon, B. S.; Perera, R.; Arachchi, W. M. Ediri; Fonseka, M. C. N.; Wettasingh, K. A.
No abstract available